2020
DOI: 10.1002/jbmr.4525
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mullerian Hormone as Predictor of Future and Ongoing Bone Loss During the Menopause Transition

Abstract: The menopause transition in women is a period of significant bone loss, with rapid declines in bone mineral density (BMD) commencing a year before the final menstrual period (FMP). Changes in menstrual bleeding patterns cannot reliably tell us if this rapid bone loss has begun or is imminent. We hypothesized that low circulating levels of anti‐Mullerian hormone (AMH), which decline as women approach the FMP, would be associated with future and ongoing rapid bone loss. We used data from The Study of Women's Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although several commercial manual and automated AMH assays are currently available, their limit of detection varies and AMH values obtained by the various assays cannot be directly compared. ( 6 ) Even though a highly sensitive AMH ELISA, which measures AMH in the pg/mL range, was used in this study by Karlamangla and colleagues, ( 8 ) the majority of late perimenopausal women had undetectable AMH levels. Although estrogen levels are still relatively stable during MT when rapid bone loss is initiated, FSH levels are increasing.…”
Section: Figmentioning
confidence: 95%
See 3 more Smart Citations
“…Although several commercial manual and automated AMH assays are currently available, their limit of detection varies and AMH values obtained by the various assays cannot be directly compared. ( 6 ) Even though a highly sensitive AMH ELISA, which measures AMH in the pg/mL range, was used in this study by Karlamangla and colleagues, ( 8 ) the majority of late perimenopausal women had undetectable AMH levels. Although estrogen levels are still relatively stable during MT when rapid bone loss is initiated, FSH levels are increasing.…”
Section: Figmentioning
confidence: 95%
“…( 9 ) In a Japanese cohort of 518 pre‐ and postmenopausal women, an AMH value below 0.08 ng/mL resulted in an odds ratio of 8.28 for early knee osteoarthritis. ( 10 ) However, the study by Karlamangla and colleagues ( 8 ) is unique as it has longitudinal AMH measurements, whereas these other studies used a single measurement. The predictive value of a single AMH measurement can be debated because it has been shown that each woman has a specific AMH decline rate.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Anti-Mullerian hormone (AMH) is a hormone secreted by the granulosa cells of the antral and small antral follicles of the ovary, which is one of the indicators of ovarian function that changes with age. 10 The concentration of AMH is decreased with age in the menopause transition of women and it has a possibility in predicting bone loss, 11 indicating that AMH is a confounder of osteoporosis. Inhibin B (InhB) is secreted by reproductive system cells, which is of great significance for maintaining female reproductive health.…”
Section: Introductionmentioning
confidence: 99%